Analisis Kreativitas Anak Usia 5-6 Tahun Ditinjau Dari Media Ecobrick : Analyze the Creativity of Children Age 5-6 Years Trough Using Ecobrick Media - Afinda Dwi Aprilian; Muhammad Nofan Zulfahmi (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
Creativity is a process to discover and produce new things that can originate from anywhere. Children between the ages of 5-6 have a self-centered creative growth that can be stimulated by games and art. Using ecobriking media is one technique to help kids who are 5-6 years old develop their creativity more. Ecobrick are a plastic waste management innovation that contains small pieces of plastic waste in used plastic bottles wich are usually used as bricks to replace building materials and can be used as a learning medium. This aims to reduce plastics waste that is difficult to decompose.  This research aimed to analyze the creativity of children age 5-6 years through using ecobrick media. This research involved 18 children age 5-6 years as a participants. This research employed a qualitative-descriptive approach. The data were obtained by using data triangulations,an observation sheet, an interview, and documentation. The data analysis conducted using an interactive model by Miles and Huberman interactive model consist of data reduction, data display, conclusion drawing, and verifiying. The findings demonstrated that children show act of clean-up mentality and are capable to make creative work of a toy airplane, out of ecobrick media according to the indicators of creative thingking skills: fluency, flexibility, originality, and elaboration.   ABSTRAK    Kreativitas adalah proses untuk menemukan dan mendatangkan hal baru yang dapat muncul dari mana saja. Perkembangan kreativitas anak usia 5-6 tahun berpusat pada diri sendiri yang dapat distimulasi melalui pendekatan karya seni dan permainan. Salah satu upaya dalam meningkatkan kreativitas anak usia 5-6 tahun yaitu pemanfaatan media ecobrick. Ecobrick merupakan inovasi pengelolaan limbah sampah plastik yang berisi potongan - potongan kecil sampah plastik ke dalam botol plastik bekas yang biasa dijadikan sebagai batu bata pengganti bahan bangunan dan dapat dimanfaatkan sebagai media pembelajaran. Hal ini bertujuan untuk mengurangi sampah plastik yang sulit terurai. Penelitian ini bertujuan untuk menganalisis kreativitas anak usia 5-6 tahun ditinjau dari media ecobrick. Subjek penelitian ini adalah 18 anak usia 5-6 tahun di TK Citra Kusuma Kecapi. Metode yang digunakan melalui pendekatan deskriptif kualitatif dengan teknik pengumpulan data triangulasi data meliputi, observasi, wawancara, dan dokumentasi. Adapun analisis data yang dilakukan menggunakan interactive model dari Miles dan Huberman dengan langkah-langkah reduksi data, penyajian data, penarikan kesimpulan, dan verifikasi data. Hasil yang diperoleh adalah anak menunjukkan sikap menjaga kebersihan dan anak mampu membuat karya kreatif pesawat mainan dari media ecobrick berdasarkan indikator berpikir kreatif diantaranya, kelancaran, kelenturan, keaslian, dan elaborasi.